Transporte público em Uberlândia: apropriação de princípios de cidades inteligentes - Shiaku, Aline Cristine (2020)
The intense and hectic population growth brings several urban problems in medium and large cities, especially regarding mobility and public transport. These problems accentuate the urgent need for measures in line with the concepts of smart cities so that there is no shortage of essential resources for the current population and future generations. Thus, this study aimed at assessing urban mobility in the city of Uberlândia (MG) focusing exclusively on public transport, according to the principles of smart cities. The research is justified by the importance of discussing urban mobility in urban centers, Uberlândia-MG being a large one, where hectic city growth leads to a wide distribution of activities throughout the territory, increasing the necessary distances traveled by people to meet their daily needs. To support the research, the theoretical framework addressed urban mobility, urban transport, regulatory aspects of mobility and finally, smart cities. The research used a qualitative bias and the strategy was grounded on a case study. As for the research objectives, it was descriptive and exploratory. For data collection, a triangulation of sources was adopted: document analysis, semi-structured interview and participant observation. Results were achieved: initially with the characterization of the city, an overview of mobility in the city and finally, analyzing how aspects of smart cities could be inserted or not in mobility. We were able to observe that some smart cities aspects have already begun to be used in Uberlândia such as: dedicated right-of-way for BRT, and a control center for monitoring and management of transport, as well as new dedicated right-of-way and terminals, still being implemented. Despite this, the city still prioritizes private vehicles, exemplified by investments in overpasses, bridges and trenches. These works only temporarily improve the mobility problems of these places, as they encourage the use of more vehicles, which will again congest, increase pollution and cause more accidents and deaths. Thus, to summarize some proposals for actions aimed at public transport and smart urban mobility, as a technological product, a booklet was developed to be presented to the Traffic and Transport Agency of Uberlândia-MG.